The Kety-Schmidt Technique for Quantitative Perfusion and Oxygen Metabolism Measurements in the MR Imaging Environment - Lee, J.J.; Powers, W.J.; Faulkner, C.B.; Boyle, P.J.; Derdeyn, C.P. (American Journal of Neuroradiology, 2013)
SUMMARY: The Kety-Schmidt technique provides quantitative measurement of whole-brain CBF. CBF is measured as the area between the arterial and venous washout curves of a diffusible tracer. Oxygen extraction and metabolism may be calculated from arterial and venous samples. In this report, we present a method for performing these measurements in an MR imaging environment. This technique could be useful for validation of MR imaging methods of hemodynamic and metabolic measurements in humans. CMRO2cerebral metabolic rate for oxygen consumptionIMintramuscularlyNDIRnondispersive infraredOEFoxygen extraction fraction